Surrogate memory: a leadership remembering a revolution for Egyptians - El-hakim, Yaseen (My University, 2023)
Egypt’s revolution in 2011 has been remembered collectively as an integral event that combines with several uprisings in other Arab states in what is known as the Arab Spring. While the event may have marked a reprieve for Egyptians from the history of persecution that past generations had been subjected to by Egyptian governments, the revolution was unsuccessful in founding a new political era for Egypt. Of the wealth of factors resulting in these circumstances, the military government’s remembering of the event has served a new authoritarian administration well as it has secured their political supremacy and altered what the revolution symbolizes for the nation. Utilizing terms and ideas from collective memory theorists and analyzing crucial events from the aftermath of the revolution, it becomes clearer how challenging it is for a revolution to be commemorated in its original form. Initially, the revolution was seen as a political rebirth for Egypt. Instead, it represented a swift reclamation of the army’s seat of power in government and subsequent self-characterization as heroes of the revolution. Amongst other things, this analysis reveals how easily interpretations of collective memory can affect, and be affected by, macro-level events in the future.
Keywords: Egypt; collective memory; power; Arab spring; revolution; commemoration; memory; remembering; narrative; popular memory